The Reappeared : Argentine Former Political Prisoners - Park, Rebekah (Book collections on Project MUSE., 2014)
Between 1976 and 1983, during a period of brutal military dictatorship, armed forces in Argentina abducted 30,000 citizens. These victims were tortured and killed, never to be seen again. Although the history of los desaparecidos, "the disappeared," has become widely known, the stories of the Argentines who miraculously survived their imprisonment and torture are not well understood. The Reappeared is the first in-depth study of an officially sanctioned group of Argentine former political prisoners, the Association of Former Political Prisoners of Córdoba, which organized in 2007. Using ethnographic methods, anthropologist Rebekah Park explains the experiences of these survivors of state terrorism and in the process raises challenging questions about how societies define victimhood, what should count as a human rights abuse, and what purpose memorial museums actually serve. The men and women who reappeared were often ostracized by those who thought they must have been collaborators to have survived imprisonment, but their actual stories are much more complex. Park explains why the political prisoners waited nearly three decades before forming their own organization and offers rare insights into what motivates them to recall their memories of solidarity and resistance during the dictatorial past, even as they suffer from the long-term effects of torture and imprisonment. The Reappeared challenges readers to rethink the judicial and legislative aftermath of genocide and forces them to consider how much reparation is actually needed to compensate for unimaginable--and lifelong--suffering.--